The Challenges of Extreme Moral Stress: Claudia Card's Contributions to the Formation of Nonideal Ethical Theory. (October 2016) - Norlock, Kathryn J.
Abstract: This essay argues that Claudia Card numbers among important contributors to nonideal ethical theory (NET), and it advocates for the worth of NET. Following philosophers including Lisa Tessman and Charles Mills, the essay contends that it is important for ethical theory, and for feminist purposes, to carry forward the interrelationship that Mills identifies between nonideal theory and feminist ethics. Card's ethical theorizing assists in understanding that interrelationship. Card's philosophical work includes basic elements of NET indicated by Tessman, Mills, and others, and further offers two important and neglected elements to other nonideal ethical theorists: (i) her rejection of the "administrative point of view, " and (ii) her focus on "intolerable harms" as forms of "extreme moral stress" and obstacles to excellent ethical lives. The essay concludes that Card's insights are helpful to philosophers in developing nonideal ethical theory as a distinctive contribution to, and as a subset of, nonideal theory.